Lucretius II - Nail, Thomas (Edinburgh University Press, 2020)
Intro -- Lucretius II -- Copyright -- Contents -- A Note on the Translation and Text -- Acknowledgements -- Preface -- Introduction -- Book III -- 1. A Matter of Desire -- 2. Kinophobia -- 3. Critique of Kinetic Reason -- 4. Dark Materialism -- 5. The Ethics of Motion -- Book IV -- 6. Ethics of the Simulacrum -- 7. All Perceptions are True -- 8. The Material Unconscious -- Conclusion -- Index.